THE INFLUENCE OF DIVIDEND POLICY, SALES GROWTH, AND AUDIT QUALITY ON TAX AGGRESSIVENESS WITH THE AUDIT COMMITTEE AS A MODERATION - Herlina Lusmeida; Patricia Charelyne Wibowo (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
The objective of this study is to empirically examine whether dividend policy, sales growth, and audit quality influence tax aggressiveness, with the contribution of the audit committee as a moderator. The sample comprises 219 observations from companies in the wholesale sub-sector within ASEAN countries during 2019–2023, selected using purposive sampling. This research employs Multiple Linear Regression Analysis and Moderated Regression Analysis. The results reveal that dividend policy, sales growth, and audit quality positively influence tax aggressiveness, while the audit committee does not directly affect tax aggressiveness. Furthermore, as a moderating factor, the audit committee does not weaken the positive relationship between dividend policy and sales growth on tax aggressiveness and does not strengthen the negative relationship between audit quality and tax aggressiveness. This study is expected to provide implications for academics as a foundation for further research by exploring other factors, for practitioners to pay more attention to handling clients and hiring accountants, and for companies as a guideline in developing corporate strategies.